Clinical Effectiveness of an Outpatient Multidisciplinary Chronic Pain Management Telementoring Service. Issue 10 (12th October 2021) - Gersch, William D.; Delate, Thomas; Bergquist, Karly M.; Smith, Karen
Abstract : Objective: The objective of this study was to assess the effectiveness of a Pain E-Consult Program (PEP), a multidisciplinary telementoring service based on the Extension for Community Healthcare Outcomes (ECHO) model to reduce opioid use in the outpatient setting. Materials and Methods: This was a retrospective matched cohort study conducted in an integrated health care delivery system. Adult patients without cancer and with a 90-day morphine milligram equivalent (MME) ≥30 mg/d between April 1, 2016, and June 30, 2017, were included. Patients whose primary care clinician received the PEP (observation) were compared with usual care (control) patients. Observation patients were matched up to 1:5 to control patients. Outcomes included change in MME and initiation of nonopioid alternative medications. Multivariable regression analyses were performed. Results: A total of 665 patients were matched: 125 and 540 in the observation and control groups, respectively. Patients were primarily female, white, and Medicare beneficiaries. The observation group had a statistically significantly greater decrease in median MME/day during the 6-month (−7.4 vs. 1.5 mg, P =0.002) and 12-month (−15.1 vs. −2.8 mg, P <0.001) follow-up and rates of ≥20% decrease (6 mo: 41.6% vs. 24.6%, P =0.003; 12 mo: 48.0% vs. 32.6%, P =0.017). There were no differences in the rates of initiation of nonopioid alternative medications. Conclusions: A PEP was associated with greater reductions in MME/day compared with usual care despite similar rates of nonopioid alternative medication initiation. A prospective randomized study of this program should be undertaken to confirm these findings.